COMPARATIVE GENOMICS USING CANDIDA ALBICANS DNA MICROARRAYS REVEALS ABSENCE AND DIVERGENCE OF VIRULENCE ASSOCIATED GENES IN CANDIDA DUBLINIENSIS - SULLIVAN, DEREK; MORAN, GARY; COLEMAN, DAVID (My University, 2004)
Candida dubliniensis is a pathogenic yeast species closely related to Candida albicans. However, it is less frequently associated with human disease and displays reduced virulence in animal models of infection. We have used comparative genomic hybridisaion (CGH) in order to discover why C. dubliniensis is apparently less virulent than C. albicans. In these experiments we compared the genomes of the two species by cohybridising C. albicans microarrays with fluorescently labeled C. albicans and C. dubliniensis genomic DNA. We found that C. dubliniensis genomic DNA hybridised reproducibly to 96% percent of C. albicans gene-specific sequences indicating a significant degree of nucleotide sequence homology (> 60%) in these sequences. The remaining 4% of sequences (representing 234 genes) gave C. albicans/C. dubliniensis normalised fluorescent signal ratios indicative of significant sequence divergence (< 60% homology) or absence in C. dubliniensis. We identified sequence divergence in several genes (confirmed by Southern Blot analysis and sequencing analysis of PCR products) with putative virulence functions including the gene encoding the hypha-specific human transglutaminase substrate Hwp1p. Poor hybridisation of C. dubliniensis genomic DNA to the secreted aspartyl proteinase encoding gene SAP5 array sequences also led us to determine that SAP5 was absent in C. dubliniensis and that this species possesses only one gene homologous to SAP4 and SAP6 of C. albicans. In addition, divergence and absence of sequences in several gene families was identified including a family of HYR1-like GPI-anchored proteins, a family of genes homologous to a putative transcriptional activator (CTA2) and several ALS genes. This study has confirmed the close relatedness of C. albicans and C. dubliniensis and has identified a subset of unique C. albicans genes that may contribute to the increased prevalence and virulence of this species.
PUBLISHED
Keywords: Candida albicans; Candida dubliniensis; Comparative genomics; Microarrays; Genes & Society; Immunology, Inflammation & Infection